Bacteremia by colistin-resistant acinetobacter baumannii isolate: a case report (2019)
Background Carbapenem-resistant Acinetobacter baumannii infections are a major public health problem worldwide, requiring the use of “old” antibiotics such as polymyxin B and E (colistin). However, there is concern regarding the emergence of isolates resistant to these antibiotics. Case presentation We report a case of a 64-year-old mestizo man hospitalized in an intensive care unit of a health institution in Colombia with identification and clinical and molecular typing of a colistin- and carbapenem-resistant A. baumannii isolate with mechanisms of resistance to colistin not previously reported, causing bacteremia. Conclusions We have identified a strain of A. baumannii with mechanisms of resistance to colistin not previously reported in a patient with bacteremia who required treatment with multiple antibiotic schemes and had an adequate response.